Anti-TNFα in inflammatory bowel disease: from originators to biosimilars - Zeng, Zhen; Lin, Hao; Jiang, Mingshan; Yuan, Jing; Li, Xi; Jia, Yongbin; Yang, Li; Zhang, Hu (Frontiers in Pharmacology, 2024)
The introduction of anti-tumor necrosis factor α (TNFα) biologics significantly innovated inflammatory bowel disease (IBD) treatment and increased medical costs. The recent expiration of patents of some anti-TNFα biologics (such as infliximab and adalimumab) facilitated the development of biosimilars. Comparable pharmacokinetic, efficacy, safety, and immunogenicity profiles between anti-TNFα originators and biosimilars were demonstrated in different studies. Anti-TNFα biosimilars hold promise for reducing the high cost of biologics and increasing patient access to biologics. In this review, we outline the current data on the use of anti-TNFα originators and biosimilars in patients with IBD, with a focus on the efficacy, safety, and immunogenicity profiles of infliximab and adalimumab biosimilars. The potential benefits, challenges, and future directions of anti-TNFα biosimilars are also discussed in the review.